Associated factors to the consumption of ultra-processed foods and its relation with dietary sources in Portugal. (7th October 2021) - Magalhães, Vânia; Severo, Milton; Correia, Daniela; Torres, Duarte; Costa de Miranda, Renata; Rauber, Fernanda; Levy, Renata; Rodrigues, Sara; Lopes, Carla
Abstract: Ultra-processed foods (UPFs) are common worldwide and associated with poorer health outcomes. This work aimed to explore the UPF consumption associated factors and its main dietary sources, by sex, in Portugal. Participants from the National Food, Nutrition and Physical Activity Survey (IAN-AF) 2015–2016, aged 3–84 years, were included ( n 5005). Dietary intake was assessed through two 1-day food diaries/24 h recalls. UPFs were identified using the NOVA classification. Associations were evaluated through linear regression models. Median UPF consumption was 257 g/d (10⋅6 % of total quantity; 23⋅8 % of total energy). Adolescents were those with higher consumption (490 g/d). Compared to adults, younger ages were positively associated with UPF consumption (e.g. adolescents (β -females: 192, 95 % confidence interval (CI): 135, 249; β -males: 327, 95 % CI: 277, 377)). A lower educational level was associated with lower UPF consumption (β -females: −63; 95 % CI: −91, −34; β -males: −68; 95 % CI: −124, −12). Also, a lower UPF consumption was observed in married males/couples compared to singles (β : −48, 95 % CI: −96, −1). Furthermore, female current/former smokers were associated with a higher UPF consumption v. never smokers (β : 79, 95 % CI: 41, 118; β : 42, 95 % CI: 8, 75, respectively). Main UPF sources were yoghurts, soft drinks and cold meats/sausages differing strongly by sex, age and education level. Yoghurts containing additives were the main contributors to the UPF consumption in children and adult females from all education ( 20 %). Soft drinks were leaders in adolescents (females: 26⋅0 %; males: 31⋅6 %) and young male adults (24⋅4 %). Cold meats/sausages stood out among low-educated males (20⋅5 %). Males, younger age groups, higher education, children with less-educated parents, married/couple males and smoking females were positively associated with UPF consumption.